Gene flow from genetically modified rice to their weedy and wild relatives and its environmental consequences - Estiati, Amy; Nugroho, Satya (ANNALES BOGORIENSES, 2009)
Rice is one of the most important food crops in the world.  Nearly half of the world population consume rice as their staple food (FAO, 2004).  With the increasing of world population, the need to provide more food supplies including rice is obvious.  Biotechnology is expected to play major roles in the improvement of crop productivity and quality. Unlike transgenic maize, eventhough many research have been done to improve rice performance by genetic engineering, transgenic rice has not been released or commercialized.  Among those research to improve rice performance are the atempt to introduce biotic and abiotic stress tolerant traits, herbicide tolerant trait and beta-carotin biosynthetic pathway.  Currently, several genetically modified rice cultivars have been and being tested on limited field trials.Keywords : Rice, stress tolerant